Anti-Atopic Dermatitis Activity of Cornus walteri and Identification of the Bioactive Compounds - Lee, Bum Soo; Cho, Ye-Ryeong; Jeong, Minju; Jang, Yoon Seo; Kim, Jin-Chul; Byun, Sanguine; Kim, Ki Hyun (MDPI, 2022)
Atopic dermatitis (AD) is a chronic inflammatory disease characterized by hyperactivated immune reactions in the skin. AD is a prevalent health concern in developing countries, with a particularly high incidence among children. Despite ongoing research on AD, prevention and treatment strategies for patients remain inadequate. In this study, the inhibitory effects of Cornus walteri on AD were investigated. C. walteri (Cornaceae), commonly known as "Walter's dogwood," is a deciduous shrub used as a traditional medicine to treat dermatologic inflammation caused by lacquer poisoning. However, the role of C. walteri in AD remains largely unknown. To evaluate its anti-AD potential, we investigated the anti-inflammatory activity of the MeOH extract of C. walteri stems (CWS) using the HaCaT human keratinocyte cell line. CWS reduced the secretion of AD-related chemokines, eotaxin-3/CCL26 and thymus and activation-regulated chemokine (TARC/CCL17). In addition, CWS also inhibited the mRNA expression of macrophage-derived chemokine (MDC/CCL22) and upregulated filaggrin, which plays an essential role in skin barrier functions. To identify the bioactive constituents of CWS, phytochemical investigation of CWS led to the isolation of potential bioactive constituents (1-6), including four triterpenoids, one steroid and one diterpene analog, the structures of which were identified as lupeol (1), betulinic acid (2), 5 alpha-stigmast-3,6-dione (3), 3-O-acetylbetulin (4), betulinic acid methyl ester (5) and norphytan (6) through nuclear magnetic resonance (NMR) spectroscopy and liquid chromatography (LC)-mass spectrometry (MS) analysis. The isolated compounds (1-6) were evaluated for their inhibitory activities against eotaxin-3 expression. Compounds 1, 2 and 3 significantly reduced the levels of eotaxin-3. These findings provided experimental evidence that CWS, particularly active compounds 1, 2 and 3, could be further utilized as potential therapeutic agents to treat AD.